Prevalence and predictors of iron deficiency anemia among pregnant women in Bolosso Bomibe district, Wolaita Zone, Southern Ethiopia Community-based cross-sectional study - Felekech Laelago; Wondimagegn Paulos; Yoseph Halala Handiso (Taylor & Francis Group, 2023)
: Iron-deficiency anemia is defined as anemia, a condition in which there less than the normal hemoglobin (Hb) accompanied by an indication of iron deficiency. Nearly half of all pregnant women worldwide suffer from anemia, and iron deficiency accounts for about half the world's anemia burden. Most of the studies conducted on iron-deficiency anemia during pregnancy were conducted at the institution level and associated factors are not well studied and documented. Hence, the aim of this study is to determine the prevalence of iron-deficiency anemia and associated factors among pregnant women in Bolosso Bomibe District, Southern Ethiopia, 2019. Community-based cross-sectional quantitative study was conducted from April to June 2019. Multistage sampling was used to include 270 study participants in 6 kebeles. The structured and pretested questionnaire, middle upper arm circumference (MUAC), Hb, serum ferritin, and C-reactive protein were used as a tool to collect data. The data was compiled and entered to EpiData version 3.1 and exported to Statistical Package for Social Sciences (SPSS) version 23.00 packages for analysis. Univariate, bivariate, and multivariable logistic regression with odds ratio along with the 95% confidence intervals (CI) was computed and interpreted. p value < 0.05 was declared as statistically significant. The prevalence of iron-deficiency anemia was 11.3% (95% CI: 8.9-15.7). Factors associated with iron-deficiency anemia were ANC follow-up for the recent pregnancy (adjusted odds ratio [AOR] = 3, 95% CI: 1.15−8.9, and years b/n successive pregnancy (AOR = 4,95% CI: 1.2-12.4). Prevalence of iron-deficiency anemia was low, which is a mild public health concern among pregnant women in Bolosso Bombe District. The factors associated with iron-deficiency anemia in this study population were MUAC, ANC follow-up, birth spacing among successive pregnancy, and duration of menstrual bleeding. Thus, there should be the integration of concerned stakeholders for implementation of different interventions to solve these problems.